PENGARUH MEDIA DIGITAL TERHADAP SIKAP KEBERAGAMAAN PESERTA DIDIK (STUDI SURVEI DI SMP AL-AKHYAR JAKARTA) - Najwa Hania Zahro; Nadiah; Kunaenih; Tasya Alifiah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The development of digital media has brought significant changes to various aspects of life, including education. In the context of Islamic Religious Education, digital media can serve as an effective learning resource that supports instructional activities while enhancing students' understanding of religious values. However, when used without proper guidance, digital media may also negatively affect students' religious attitudes. Therefore, this study aims to examine the influence of digital media on the religious attitudes of students at SMP Al-Akhyar Jakarta. This study employed a quantitative method with a descriptive correlational approach. The research population consisted of 86 eighth-grade students of SMP Al-Akhyar Jakarta in the 2025/2026 academic year, all of whom were selected as the research sample. Data were collected through questionnaires, interviews, observations, and documentation, while data were analyzed using descriptive statistics and the Pearson Product-Moment correlation test. The findings indicate that digital media has a positive and statistically significant influence on students' religious attitudes. This is evidenced by a correlation coefficient (r) of 0.464, indicating a moderate level of correlation, and a significance value of 0.000 (< 0.05), leading to the rejection of the null hypothesis (H₀) and the acceptance of the alternative hypothesis (Hₐ). Furthermore, the coefficient of determination (R²) of 21.6% indicates that digital media accounts for 21.6% of the variance in students' religious attitudes, while the remaining 78.4% is attributable to other factors beyond the scope of this study, including family environment, school environment, peer influence, and individual characteristics. These findings suggest that the appropriate use of digital media, supported by guidance from teachers and parents, can contribute to strengthening students' religious attitudes. Therefore, collaboration between schools and parents is essential to promote digital literacy and encourage the constructive use of digital media in supporting learning activities and reinforcing religious values.